Decoding the Code of Silence. (March 2018) - Kutnjak Ivković, Sanja; Haberfeld, Maki; Peacock, Robert
The code of silence—the informal prohibition of reporting misconduct by fellow police officers—has long been viewed as a serious obstacle in control of police misconduct and achievement of police accountability. The purpose of this article is to study the key correlates of police officers' reluctance to report. Relying upon a theory of police integrity and the accompanying methodology to study the code, a police integrity survey was administered in 2013 and 2014 to measure the contours of police integrity among 604 police officers from 11 police agencies located in the Midwest and the East Coast of the United States. The questionnaire contains descriptions of 11 scenarios describing various forms of police misconduct, each followed by seven questions measuring officer views of scenario seriousness, the appropriate and expected discipline, and willingness to report misconduct. Multivariate analyses reveal that the key factor related to the police officers' reluctance to report is the perception that the other officers would not report. The code is also negatively related to familiarity with the official rules, evaluation of misconduct as serious, and the expectation of harsher discipline. The methodology can be used either by the police agencies themselves or by the civilian oversights to assess the nature and extent of the code in the police agency.